Analysis of Infant Foods using Energy Dispersive X-Ray Fluorescence Spectrometry - Ekinci, N.; Dogan, B.; Han, I.; Agbaba, M. (Asian Journal of Chemistry, 2011)
The present work aims at the determination of detection limits of the various infant foods from Turkey using energy dispersive X-ray fluorescence spectrometer (EDXRF). The X-ray spectra were collected using a Si(Li) detector coupled with Canberra DSA-1000 desktop spectrum analyzer and a 55Fe annular radioactive source. The relative errors for the detection limit measurements of 55Fe radioactive source were found within 2-6 %. From the results, it can be concluded that the infant foods are rich in elements such as chlorine, potassium and calcium. Finally, the EDXRF technique was found to be sensitive and readily applicable for the determination of detection limit in various infant foods.